2023
DOI: 10.1097/aog.0000000000005153
|View full text |Cite
|
Sign up to set email alerts
|

Abortion Access and Medically Complex Pregnancies Before and After Texas Senate Bill 8

Abstract: Restrictive abortion policies did not align with health care professionals' more nuanced views of options for care and patient autonomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Prior to the Dobbs decision, people criminalized for self‐managed abortions were often discovered when health care professionals reported them to legal authorities, believing that such reporting was required 163 . In a post‐ Dobbs iteration of this gatekeeping role, when states allow only very narrow exceptions to abortion bans, physicians struggle to understand whether and when they can offer the standard of care—which includes abortion—in medically complicated pregnancies 164 . Abortion law, in other words, produces physicians and other healthcare professionals as state actors.…”
Section: Abortion Law and Societymentioning
confidence: 99%
“…Prior to the Dobbs decision, people criminalized for self‐managed abortions were often discovered when health care professionals reported them to legal authorities, believing that such reporting was required 163 . In a post‐ Dobbs iteration of this gatekeeping role, when states allow only very narrow exceptions to abortion bans, physicians struggle to understand whether and when they can offer the standard of care—which includes abortion—in medically complicated pregnancies 164 . Abortion law, in other words, produces physicians and other healthcare professionals as state actors.…”
Section: Abortion Law and Societymentioning
confidence: 99%
“…Policies out of step with the complexity of medical practice make it difficult to provide evidence-based health care. In the state of Texas, where abortion is illegal except in the cases of life endangerment, a qualitative study of health care professionals showed that hospital policies after Senate Bill 8 limited health care options, even when medical conditions placed the patient at risk of death 13 . Many health care providers expressed fear of discussing abortion with patients due to the implication that they could be aiding and abetting an illegal abortion.…”
Section: Policy and Public Opinionmentioning
confidence: 99%
“…In many states, current abortion policy puts health care providers at risk of lawsuits, loss of medical licensure, fines, or imprisonment. Even in exceptional cases when care is permitted, providers must prepare careful documentation and may be forced to seek legal and/or ethics consultations or a second provider’s opinion before offering therapy, further delaying the delivery of potentially life-saving medical care 13 . In this landscape, providers may modify care plans when treating pregnant patients, even in emergent situations, out of fear of legal ramifications.…”
Section: Abortion Policy: Clinical Considerationsmentioning
confidence: 99%
See 2 more Smart Citations